Vertical crown fuel distributions in natural Calabrian pine (Pinus brutia Ten.) stands - Baysal, İsmail (Array, 2021)
Calabrian pine (Pinus brutia Ten.) is the most widely distributed coniferous species in Turkey. Forests mostly composed of Calabrian pine constitute the most flammable forests in fire sensitive regions of the country. Especially, regenerated and immature stands of this species have the most fire-prone fuel type. This study evaluates the results of vertical crown fuel distribution and develops some crown fuel models to explain canopy fuel characteristics in natural Calabrian pine stands. A total of 35 trees were cut down and crown fuels were determined vertically. The highest crown fuel load was generally situated in the middle part of tree crown. The percentage of needles in each crown section increased gradually from the beginning of lower parts to the upper parts of tree crowns for three stand types. Total crown fuel loads were determined as 5.66 kg for regenerated stands, 11.57 kg for immature stands and 17.44 kg for middle age stands, respectively. Correlation and regression analyses were performed to determine the relationship between needles, branches, available fuels, total crown fuels and tree properties. The results of crown fuel distribution and the allometric equations developed in this study can be used to predict vertical fuel load at any height from ground to the top of Calabrian pine stands. The results of this study will contribute to the verification and evaluation of fuel load prediction models in use, and enhance the understanding of crown fire behavior mechanism in forest fires.